Teachers' perceptions of student engagement and teacher self-efficacy beliefs - Pappa, Sotiria (2014)
This study examines the teachers’ perceptions of student engagement, teachers’ self-efficacy beliefs, and their interrelation. Affective engagement can be understood as belonging or relatedness as well as identification with school. Cognitive engagement can be conceived as engagement in classroom, self-regulation, learning goals and a student’s overall investment in learning. Measuring students’ engagement is crucial in that it helps educators predict and, by amending current teaching practices and policies, avoid poor performance or even drop-out. The teacher’s belief in herself and her potential is critical for the students’ overall performance in class. This study attempts to investigate the relationship between these two concepts and hopes to reveal their impact on the teaching quality.